MATLAB Codes for Finite Element Analysis - Ferreira, A. J. M. (Springer, 2017)
This book illustrates how MATLAB compact and powerful programming framework can be very useful in the finite element analysis of solids and structures. The book shortly introduces finite element concepts and an extensive list of MATLAB codes for readers to use and modify. The book areas range from very simple springs and bars to more complex beams and plates in static bending, free vibrations and buckling problems.